2014
DOI: 10.1097/mph.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Being Overweight and Obese at Diagnosis in Children With Acute Lymphoblastic Leukemia

Abstract: This study tested the hypothesis that being overweight/obese at diagnosis of childhood ALL was related to risk of relapse. In a national cohort of 1033 patients from the UK, there was no evidence that weight status at diagnosis was related significantly to risk of relapse: log-rank test (P=0.90) with overweight and obesity as the exposure (n=917); individual (P=0.42) and stepwise (P=0.96) proportional hazards models, with BMI Z score as the exposure. The study does not support the hypothesis that being overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…This study found that obesity was associated with a significantly increased risk of relapse, particularly in children over 10 years of age (considered high risk). This latter caveat is consistent with the findings of a relatively small study of 337 patients from the UKALL X treatment trial, which included only standard risk patients, and concluded that overweight or obesity at diagnosis was unlikely to impair prognosis (20). Thus, it appears that obesity can impair ALL outcome at least in high risk, older patients.…”
Section: Does Obesity Directly Increase Leukemia Mortality?supporting
confidence: 83%
“…This study found that obesity was associated with a significantly increased risk of relapse, particularly in children over 10 years of age (considered high risk). This latter caveat is consistent with the findings of a relatively small study of 337 patients from the UKALL X treatment trial, which included only standard risk patients, and concluded that overweight or obesity at diagnosis was unlikely to impair prognosis (20). Thus, it appears that obesity can impair ALL outcome at least in high risk, older patients.…”
Section: Does Obesity Directly Increase Leukemia Mortality?supporting
confidence: 83%
“…Studies that showed that baseline BMI was not associated with outcome included small numbers of patients in BMI subgroups, or only analyzed the influence of being overweight on survival. [5][6][7][8]13 Studies that reported baseline undernourishment as a determinant of impaired survival were mostly conducted in developing countries or had small numbers in the BMI subgroups. [9][10][11] In those series, patients were, in addition to their disease status and treatment, also coping with additional risk factors for poor outcome such as malnutrition and poor socioeconomic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies in pediatric ALL showed contradictory results, i.e. some studies show that weight at diagnosis does not influence survival, while others suggest that being underweight or overweight at diagnosis of ALL has an influence on survival [4][5][6][7][8][9][10][11][12][13][14] (Table 1). Body composition changes extremely during the treatment of pediatric ALL due to the use of corticosteroids, 15,16 but also due to other factors such as the catabolic effect of the disease itself, stress, 17 nutritional changes and impaired exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Partial cystectomies have only been carried out in high grade cases [33,36] and where anatomically it was reported to be difficult for adequate endoscopic resection [33].…”
Section: Discussionmentioning
confidence: 99%
“…Only one paper has reported the use of MVAC (Methotrexate, Vinblastine, Adriamycin and Cisplatin) [35]. As the rates of recurrence seem to be so low in general, this supports the current trend to hold off using adjuvant chemotherapy in this age group and avoid further invasive treatment and its side-effects [33]. However, the evidence regarding prognosis is currently too weak for any solid recommendations to be made.…”
Section: Discussionmentioning
confidence: 99%